Recurrent vaginal cuff dehiscence after surgery for endometriosis: a technique for laparoscopic repair with an omental flap - Frank, Gerard-Peter (BMJ Case Rep, 2021)
Vaginal evisceration is a rare but severe complication after hysterectomy or colpotomy and is generally successfully repaired by reapproximating healthy tissue edges of the vagina. Recurrent vaginal cuff dehiscence is problematic especially in sexually active women. We describe two cases of recurrent vaginal cuff dehiscence. The first patient had a hysterectomy for endometriosis. The second patient underwent laparoscopic excision of an endometriotic nodule at the vaginal vault. The vaginal cuff dehiscence was repaired by a laparoscopic approach employing an omental flap to enhance tissue healing. This closure technique turned out to be successful at follow-up in both cases. In case of recurrent vaginal cuff dehiscence, management options are limited. Our case report offers a laparoscopic treatment option by using an omental flap. This procedure can be used when conventional repair fails.